A fully battery-powered inexpensive spectrophotometric system for high-sensitivity point-of-care analysis on a microfluidic chip. Issue 12 (4th May 2016) - Dou, Maowei; Lopez, Juan; Rios, Misael; Garcia, Oscar; Xiao, Chuan; Eastman, Michael; Li, XiuJun
Abstract : A low-cost b̲a̲ttery-powered s̲pectrophotometric s̲ystem (BASS) was developed for high-sensitivity point-of-care analysis in low-resource settings on a microfluidic chip without relying on external power supplies. Abstract : A cost-effective b̲a̲ttery-powered s̲pectrophotometric s̲ystem (BASS) was developed for quantitative point-of-care (POC) analysis on a microfluidic chip. By using methylene blue as a model analyte, we first compared the performance of the BASS with a commercial spectrophotometric system, and further applied the BASS for loop-mediated isothermal amplification (LAMP) detection and subsequent quantitative nucleic acid analysis which exhibited a comparable limit of detection to that of Nanodrop. Compared to the commercial spectrophotometric system, our spectrophotometric system is lower-cost, consumes less reagents, and has higher detection sensitivity. Most importantly, it does not rely on external power supplies. All these features make our spectrophotometric system highly suitable for a variety of POC analyses, such as field detection.